2021
DOI: 10.13057/biodiv/d220402
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of blaCTX-M and blaTEM genes encoding extended-spectrum ß-lactamase (ESBL) producing Escherichia coli isolated from raw cow’s milk in East Java, Indonesia

Abstract: Abstract. Ansharieta R, Ramandinianto SC, Effendi MH, Plumeriastuti H. 2021. Molecular identification of blaCTX-M and blaTEM genes encoding extended-spectrum ß-lactamase (ESBL) producing Escherichia coli isolated from raw cow’s milk in East Java, Indonesia. Biodiversitas 22: 1600-1605. The emergence of extended-spectrum ?-lactamase (ESBL) producing bacteria and its increasing level has become public health issue. The presence of these bacteria in food of animal origin is quite alarming. The objective of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 21 publications
(27 reference statements)
1
23
2
Order By: Relevance
“…The prevalence of the blaTEM genes in ESBLproducing E. coli was 3 (1.7%). This finding is in line with the research conducted by Ansharieta et al [21], who stated that E. coli contamination found in milk from dairy farms tends to encode the blaTEM gene in ESBL-producing E. coli bacteria. These results show that pathogenic E. coli originating from food of animal origin are also exposed to antibiotics and can transfer these genes to other pathogenic bacteria under certain conditions [45].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The prevalence of the blaTEM genes in ESBLproducing E. coli was 3 (1.7%). This finding is in line with the research conducted by Ansharieta et al [21], who stated that E. coli contamination found in milk from dairy farms tends to encode the blaTEM gene in ESBL-producing E. coli bacteria. These results show that pathogenic E. coli originating from food of animal origin are also exposed to antibiotics and can transfer these genes to other pathogenic bacteria under certain conditions [45].…”
Section: Discussionsupporting
confidence: 92%
“…The ESBL-producing E. coli detected was further examined at a molecular level. Bacterial DNA was extracted using the QIAamp DNA Mini Kit (Promega) protocol according to Kristianingtyas et al [19], and the blaTEM gene was detected using the PCR method as described by Putra et al [20] and Ansharieta et al [21] as indicated in Table -1. After the amplification, products were visualized by exposure of the gel to ultraviolet light and subsequently photographed and documented using agel documentation system (Promega).…”
Section: Confirmation Test For Extended-spectrum Beta-lactamase (Esbl...mentioning
confidence: 99%
“…The relative abundance of the ESBL producing E. coli in samples poultry has been shown to vary with geographic location (Wibisono et al 2020d). In this study, isolates including ESBL producing E. coli were detected by DDST (Ansharieta et al 2021a). Molecular identification showed that 25 (73,5%) samples of ESBL producing E. coli encoding iss gene, and 1 (2,9%) sample of ESBL producing E. coli encoding papC gene (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Infectious diseases involve the causative agent and host, as well as environmental factors. Diseases caused by Escherichia coli are disease agents that are often faced by all livestock farms, especially poultry farms, therefore knowledge, and information about disease incidence and prevention, control, and eradication efforts are needed (Putra et al 2020;Wibisono et al 2020b;Ansharieta et al 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…Asia is one of the epicenters of antibiotic resistance, there are a surprising number of drug-resistant strains, including K. pneumoniae, and a large number of acquired Gramnegative MDR strains have been found (Jean and Hsueh 2011). AMR can be disseminated rapidly through a variety of possible pathways, including foodborne pathogens, insects, wastewater, pets, food producers or wild animals Ansharieta et al 2021). In particular, more than 25 outbreaks of human infectious disease outbreaks were reported, 11 associated with animals on farms, and zoos from 1990 to 2000 (Bender and Shulman 2004).…”
Section: Have Been Found To Be Infected With Esblproducingmentioning
confidence: 99%